Fungal diversity on fallen leaves of Ficus in northern Thailand - Wang, Hong kai; Hyde, Kevin D.; Soytong, Kasem; Lin, Fu Cheng (My University, 2008)
Fallen leaves of Ficus altissima, F. virens, F. benjamina, F. fistulosa and F. semicordata, were collected in Chiang Mai Province in northern Thailand and examined for fungi. Eighty taxa were identified, comprising 56 anamorphic taxa, 23 ascomycetes and 1 basidiomycete. Common fungal species occurring on five host species with high frequency of occurrence were Beltraniella nilgirica, Lasiodiplodia theobromae, Ophioceras leptosporum, Periconia byssoides and Septonema harknessi. Colletotrichum and Stachybotrys were also common genera. The leaves of different Ficus species supported diverse fungal taxa, and the fungal assemblages on the different hosts showed varying overlap. The fungal diversity of saprobes at the host species level is discussed. © Zhejiang University and Springer-Verlag GmbH 2008.
Keywords: Fallen leaves; Ficus; Fungal diversity; Saprobes